2020
DOI: 10.32698/0982
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of Parents Attention to Student Achievement Motivation

Abstract: The low student achievement motivation is something that must be considered. Parents attention became one of the factors that can influence student achievement motivation. The purpose of this study to describe the contribution of parent attention to student’s achievement motivation in SMK Muhammadiyah 1 Padang. This research uses regression analysis. In the research took the sample of 233 students by using purposive sampling technique. It was used instrument "Wira Solina Parents Attention Scale" with reliabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 43 publications
(45 reference statements)
0
4
0
1
Order By: Relevance
“…Based on the questionnaire result, the parents in the school of the coastal area still need more understanding of the importance of parents' role to motivate their children to learn English. Parents should not only accompany their children when their children did not understand the lesson but accompanying them when learning can also bring a significant impact and excel the students' education (Nofrizal et al, 2020). It has been proved by previous studies that parents' involvement when children learning affects children's achievement (Alfiansyah, 2019;Bonjoc et al, 2019;Klaver et al, 2022;Rosyidah & Sari, 2020;Siti et al, 2022).…”
Section: T H E P a R E N T S ' R O L E C A T E G O R Ymentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the questionnaire result, the parents in the school of the coastal area still need more understanding of the importance of parents' role to motivate their children to learn English. Parents should not only accompany their children when their children did not understand the lesson but accompanying them when learning can also bring a significant impact and excel the students' education (Nofrizal et al, 2020). It has been proved by previous studies that parents' involvement when children learning affects children's achievement (Alfiansyah, 2019;Bonjoc et al, 2019;Klaver et al, 2022;Rosyidah & Sari, 2020;Siti et al, 2022).…”
Section: T H E P a R E N T S ' R O L E C A T E G O R Ymentioning
confidence: 99%
“…Many researchers have investigated the teacher's role in formal or informal education (Alfiansyah, 2019;Beatus et al, 2020;Mardiani, 2021;Nofrizal et al, 2020;Rosyidah & Sari, 2020). Those researchers investigated the parents' involvement related to their children's motivation at school.…”
Section: Introductionmentioning
confidence: 99%
“…Kedua penelitian ini menunjukkan bahwa lingkungan keluarga mempunyai pengaruh yang signifikan terhadap prestasi belajar siswa. Begitu pula hasil penelitian Nofrizal et al (2020) menunjukkan bahwa perhatian orang tua (ayah dan ibu) dapat meningkatkan motivasi berprestasi siswa, sehingga disarankan untuk melibatkan orang tua untuk meningkatkan motivasi berprestasi siswa.…”
Section: Dukunganunclassified
“…Motivation has a significant correlation with individuals’ behavior, to be specific, positive motivation is able to stimulate good behavior, while negative motivation holds back such behavior ( Chiang et al, 2018 ). Achievement motivation has an impact on students’ success and excellence in the process of academic study ( Nofrizal et al, 2020 ), which, in turn, influences their employment prospects upon graduation ( Kamaliah et al, 2018 ). Prior studies have confirmed that achievement motivation significantly impacts the employability of college students, but only a few studies investigated the underlying mechanism of such influence.…”
Section: Introductionmentioning
confidence: 99%